Differentially expressed gene profiles and associated ceRNA network in ATG7-Deficient lens epithelial cells under oxidative stress - Li, Hongyu; Gao, Lixiong; Du, Jinlin; Ma, Tianju; Ye, Zi; Li, Zhaohui (Frontiers in Genetics, 2022)
Oxidation is an essential factor during cataract development. Autophagy, usually a cytoprotective process, is always found elevated in lens epithelial cells under oxidation, yet its roles and associated molecular mechanisms under such circumstances are rarely elucidated. Herein, we extracted and re-analyzed the RNA sequencing data of the GSE161701 dataset from the Gene Expression Omnibus database to identify the differentially expressed mRNAs and lncRNAs by using the R package “DESeq2”. Further analyses of gene ontology and KEGG enrichment were implemented via the packages “clusterProfiler” and “enrichplot”. We found that after the knockout of ATG7, differentially expressed genes were more associated with hemopoiesis, vasculature development, axonogenesis, and hypoxia regulation. When stimulated with H2O2, LECs displayed a gene expression profile correlating with apoptotic and proliferative pathways, such as the MAPK signaling pathway and FoxO signaling pathway. The differentially expressed gene profiles of the two types of LECs (wild type and ATG7 deficient) under oxidation were distinct to a large extent. Furthermore, 1,341 up-regulated and 1912 down-regulated differential mRNAs and 263 up-regulated and 336 down-regulated differential lncRNAs between these two types of LECs subjected to H2O2 were detected, among which 292 mRNAs and 24 lncRNAs possibly interacted with ten cataract-related miRNAs. A competing endogenous lncRNA-miRNA-mRNA network based on such interactions was finally constructed.